A Causal Model of Psychosocial factors for Empowering Thai Youth in Preventing Domestic Violence - Nonthachot, Perawat; Yaemyuean, Anan; Uansa-ard, Suwaluck (The Journal of Behavioral Science, 2023)
Domestic violence has an impact on behavior, particularly in young children who grow up in families where violence is highly likely in the new normal age. This research aimed study direct and indirect influences of psychological traits and situations on behavior of empowerment for violence -free family in the new normal among Thai youth. The samples in his research included 450 Thai youths who were randomly selected with multistage quota random sampling method. The variables included exogenous latent variables: psychological traits, situations and psychological states, and endogenous latent variables: behavior of empowerment for violence -free family and psychological states. The result of testing the causal model of all variables was harmonized with empirical data (Chi-square = 219.98, df = 98, GFI = .95, CFI = .97, NFI = .95, AGFI = .92, RMSEA =.053, and SRMR =.036). The psychological traits and situations had direct influence on the psychological states (β =.38 and β =.47, respectively) while the situations and psychological states directly influenced the behavior of empowerment for violence -free family (β =.83 and β =.67, respectively). However, the psychological traits had no direct influence on the behavior of empowerment for violence -free family (β =-2.41).